Endometrial Stromal Sarcoma in Term Pregnancy: A Unique Case Report and Review of the Literature - Koulaymi, Eva; Khairallah, Mayssaloun; Haroun, Zeinab; Kassab, Kawthar; Al Hassan, Jihad; Khazaal, Janoub; Wehbe, Georges; Nasser, Lilian (International Journal of Clinical Research, 2024)
Background: Endometrial stromal sarcoma (ESS)is a rare malignancy described only in a limited number of case reports. It accounts for only 2% of all uterine tumors. Case Report: We describe a case of a 29-year-old pregnant lady presenting at 37 weeks of gestation in labor. A huge intra-cavitary mass was seen on bedside ultrasound upon her presentation. The patient underwent an urgent repeat cesarean section where a twenty cm uterine mass was identified after delivering the baby and the placenta. The pathology exam of the group showed low-grade endometrial stromal sarcoma with anti-CD10 and anti-estrogen receptors. A radical hysterectomy with bilateral salpingo-oophorectomy was performed two days later as the ESS was staged 1B following the post-cesarean PET scan result. Conclusion: ESS is infrequent in young women as well as pregnant patients. This is the first case of asymptomatic endometrial stromal sarcoma in pregnancy, giving birth to a full-term baby with successful treatment.